ENVIRONMENTAL DATA AND DIGITAL TWINS FOR ROAD TRAFFIC SAFETY IN RURAL AREAS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In this article, the critical factors of the road traffic safety in rural areas are reviewed. The critical factors and related information from open data and environmental data are analysed and the meta model is created for processing of road traffic safety data in rural areas. Later on the basis of meta model the Digital Twin is created that could be used for an improvement of the traffic safety on the rural area roads in Latvia. An open data analysis is performed that concludes the opportunities to improve the potential of Latvian traffic accident open data.